Use of Computational Methods To Understand The Pattern Of Antimicrobial Resistance - Chio, Hok In (2024)
Antimicrobial resistance (AMR) as one of the most serious problems in the world is especially urgent with the increase in antibiotic resistance of bacteria across the world. Antibiotics reach the environment via excretions from humans and agriculture, and industrial and hospital waste products. The environmental concentrations of antibiotics are usually much lower than the minimal inhibitory concentrations and most often lower than concentrations predicted to select for resistant strains in the laboratory. However, exposure to low levels of antibiotics has also been shown to increase resistance, resulting in the increase of selective pressure.